Sensitivity to CP $$ \mathcal{CP} $$ -violating effective couplings in the top-Higgs sector - Víctor Miralles; Yvonne Peters; Eleni Vryonidou; Joshua K. Winter (Journal of High Energy Physics)
Abstract The observed baryon asymmetry of the Universe requires new sources of charge-parity ( CP $$ \mathcal{CP} $$ ) violation beyond those in the Standard Model. In this work, we investigate CP $$ \mathcal{CP} $$ -violating effects in the top-Higgs sector using the Standard Model Effective Field Theory (SMEFT) framework. Focusing on top-pair production in association with a Higgs boson and single top-Higgs associated production at the LHC, we study CP $$ \mathcal{CP} $$ violation in the top-Higgs Yukawa coupling and other Higgs and top interactions entering these processes. By analysing CP $$ \mathcal{CP} $$ -sensitive differential observables and asymmetries, we provide direct constraints on CP $$ \mathcal{CP} $$ -violating interactions in the top-Higgs sector. Our analysis demonstrates how combining t t ¯ h $$ t\overline{t}h $$ and thj production can disentangle the real and imaginary components of the top-Yukawa coupling, offering valuable insights into potential sources of CP $$ \mathcal{CP} $$ violation. The sensitivity of these observables to SMEFT operators provides model-independent constraints on the parameter space, advancing the search for new physics in the top-Higgs sector.